2012
DOI: 10.1016/j.eneco.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Population density and efficiency in energy consumption: An empirical analysis of service establishments

Abstract: The achievement of both sustainable economic growth and reductions in CO 2 emissions has been an important policy agenda in recent years. This study, using novel establishment-level microdata from the Energy Consumption Statistics, empirically analyzes the effect of urban density on energy intensity in the service sector. According to the analysis, the efficiency of energy consumption in service establishments is higher for densely populated cities. Quantitatively, after controlling for differences among indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 22 publications
2
37
2
Order By: Relevance
“…Glaeser and Kahn (2010) find that large, dense cities in the US produce fewer GHG emissions. Morikawa (2013) finds that dense cities in Japan produce lower per capita energy consumption in the service sector, and Blaudin de Thé and Lafourcade (2016) show that residents of low density suburban households use more gasoline for driving. Larson and Yezer (2015) study the effect of city size on energy use in a simulation model, finding that per capita energy use does not change with city size.…”
Section: Introductionmentioning
confidence: 99%
“…Glaeser and Kahn (2010) find that large, dense cities in the US produce fewer GHG emissions. Morikawa (2013) finds that dense cities in Japan produce lower per capita energy consumption in the service sector, and Blaudin de Thé and Lafourcade (2016) show that residents of low density suburban households use more gasoline for driving. Larson and Yezer (2015) study the effect of city size on energy use in a simulation model, finding that per capita energy use does not change with city size.…”
Section: Introductionmentioning
confidence: 99%
“…Considering traffic congestion and highway density as part of the urban structure, Su showed that population density negatively affects household gasoline consumption. Morikawa [25] and Otsuka and Goto [26,27] examined the effect of population density on energy efficiency and demonstrated that energy efficiency improved when the population density increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study considered traffic congestion and highway density as part of the urban structure, and showed that population density negatively affected household petrol consumption. Morikawa () looked at the service sector in Japan and examined the effect of population density on energy efficiency. He demonstrated that the energy efficiency improved by about 12 per cent when the population density doubled.…”
Section: Literature Reviewmentioning
confidence: 99%